Вплив біологічнофункціональних речовин на ріст пшениці та склад мікрофлори її різосфери - Тугай, Т.І.; Трач, В.В.; Лопатько, К.Г.; Тугай, А.В.; Наконечна, Л.Т. (Фактори експериментальної еволюції організмів, 2015)
Aims. Comparative study of the influence of nanoparticles and in combination with the Baikal EM intensity on growth of wheat (an increase in mass of the ground and root weight) and the number of main ecological and trophic groups of microorganisms: pedotrofy, amylolytic, nitrogen fixation, phosphate mobilization, cellulose lytic bacteria. Methods. Experiments were performed in terms of experience with growing wheat plants (variety «Natsyonalnaya»). Plants were grown in 5-kg tanks (black earth, sand in the ratio 3:1). Treated by spraying colloidal solutions of magnesium and iron (0.1 mg / l), the «Baikal EM» (0.1 % solution) in a phase 3 true leaves. Results. Both studied, preparation nanoparticles of magnesium and iron and range of these solutions with the preparation Baikal EM stimulated growth herbal weight and length of the roots of wheat. These two preparation affect different ecological trophic groups. Conclusions. Both studied, nanoparticles of magnesium and iron and range of these solutions with the Baikal EM stimulated growth herbal weight and length of the roots of wheat. Treatment of nanoparticles led to an increase in all studied ecological trophic groups of microorganisms: pedotrofy, amylolytic, nitrogen fixation, phosphate mobilization, cellulose lytic bacteria. With the impact of several and nanoparticles Baikal EM only observed increase of amylolytic and cellulose lytic bacteria. Keywords: nanoparticles, pedotrofy, amylolytic, nitrogen fixation, phosphate mobilization, cellulose lytic bacteria.